Cellular Mechanisms of Human Atherogenesis: Focus on Chronification of Inflammation and Mitochondrial Mutations - Markin, Alexander M.; Sobenin, Igor A.; Grechko, Andrey V.; Zhang, Dongwei; Orekhov, Alexander N. (Frontiers in Pharmacology, 2020)
Atherosclerosis is one of the most common diseases of the cardiovascular system that leads to the development of life-threatening conditions, such as heart attack and stroke. Arthrosclerosis affects various arteries in the human body, but is especially dangerous affecting arteries alimenting heart and brain, aorta and arteries of the lower limbs. By its pathophysiology, atherosclerosis is an inflammatory disease. During the pathological process, lesions of arterial intima in the form of focal thickening are observed, which form atherosclerotic plaques as the disease progresses further. Given the significance of atherosclerosis for the global health, the search for novel effective therapies is highly prioritized. However, despite the constant progress, our understanding of the mechanisms of atherogenesis is still incomplete. One of the remaining puzzles in atherosclerosis development is the focal distribution of atherosclerotic lesions on the arterial wall. It implies the existence of certain mosaicism within the tissue, which may prove to be important for novel therapy development. There are many hypotheses explaining this phenomenon, for example, the influence of viruses, and the spread in the endothelium of the vessel multinucleated giant endothelial cells. We suggest the local variations of the mitochondrial genome as a possible explanation of this mosaicism. In this review, we discuss the role of genetic variations in the nuclear and mitochondrial genomes that influence the development of atherosclerosis. Changes in the mitochondrial and nuclear genome have been identified as independent factors for the development of the disease, as well as potential diagnostic markers.